CREG1 Interacts with Sec8 to Promote Cardiomyogenic Differentiation and Cell‐Cell Adhesion. (8th July 2016) - Liu, Jie; Qi, Yanmei; Li, Shaohua; Hsu, Shu‐Chan; Saadat, Siavash; Hsu, June; Rahimi, Saum A.; Lee, Leonard Y.; Yan, Chenghui; Tian, Xiaoxiang; Han, Yanling
Abstract: Understanding the regulation of cell‐cell interactions during the formation of compact myocardial structures is important for achieving true cardiac regeneration through enhancing the integration of stem cell‐derived cardiomyocytes into the recipient myocardium. In this study, we found that cellular repressor of E1A‐stimulated genes 1 (CREG1) is highly expressed in both embryonic and adult hearts. Gain‐ and loss‐of‐function analyses demonstrated that CREG1 is required for differentiation of mouse embryonic stem (ES) cell into cardiomyocytes and the formation of cohesive myocardium‐like structures in a cell‐autonomous fashion. Furthermore, CREG1 directly interacts with Sec8 of the exocyst complex, which tethers vesicles to the plasma membrane. Site‐directed mutagenesis and rescue of CREG1 knockout ES cells showed that CREG1 binding to Sec8 is required for cardiomyocyte differentiation and cohesion. Mechanistically, CREG1, Sec8, and N‐cadherin colocalize at intercalated discs in vivo and are enriched at cell‐cell junctions in cultured cardiomyocytes. CREG1 overexpression enhances the assembly of adherens and gap junctions. By contrast, its knockout inhibits the Sec8‐N‐cadherin interaction and induces their degradation. These results suggest that the CREG1 binding to Sec8 enhances the assembly of intercellular junctions and promotes cardiomyogenesis. Stem Cells 2016;34:2648–2660 Abstract : Schematic model for a role of CREG1 in the formation of intercalated discs between cardiomyocytes. During cardiomyocyte differentiation from embryonic stem cells, CREG1 is upregulated and binds to Sec8 of the exocyst complex. The CREG1‐exocyst interaction increases the delivery of N‐cadherin from intracellular compartments, such as Golgi and recycling endosomes (ER), to the cell‐cell adhesion sites, thereby promoting the formation of intercalated discs.